Tapered Cuff versus Conventional Cuff for Ventilator-Associated Pneumonia in Ventilated Patients: A Meta-Analysis of Randomized Controlled Trials - Wei Min Huang; Xu An Huang; Yan Ping Du; Liu Xia Li; Fang Fang Wu; Shao Qing Hong; Fang Xuan Tang; Zhang Qiang Ye (Canadian Respiratory Journal)
Background. Microaspiration of secretions around the tracheal cuff is a multifactorial process. Tracheal cuff shape might take a major part in its occurrence. The rationale for producing a taper-shaped cuff is established on the assumption that compared to a conventional cuff with a single fixed diameter, a continuum of minimum-to-maximum diameter sections might better fit the tracheal walls. Objectives. The primary objective of this meta-analysis was to compare ventilator-associated pneumonia (VAP) between tapered-cuff intubation and conventional-cuff intubation. The secondary objective was to compare intensive care unit (ICU) mortality between tapered-cuff intubation and conventional-cuff intubation. Methods. We searched the Cochrane Library, Embase, MEDLINE database through the PubMed search engine, and CINAHL from inception to April 2018. Randomized trials comparing VAP and ICU mortality between tapered-cuff intubation and conventional-cuff intubation in intubated adults were included. Two review authors assessed study quality and abstracted databasing on prespecified criteria independently. Results. We pooled summary estimates from 5 trials evaluating tapered-cuff involving 774 participants. Compared to VAP, no statistically significant difference was observed between the tapered-cuff and conventional-cuff groups (OR 0.82, CI 0.61–1.12, z = 1.24, and p=0.21). No statistically significant difference was observed between the tapered-cuff and conventional-cuff groups with ICU mortality (OR 0.77, CI 0.55–1.08, z = 1.49, and p=0.14). Conclusions. In this meta-analysis, the tapered-cuff tracheal tube may not be superior to the standard-cuff tracheal tube in reducing VAP and ICU mortality.